2008
DOI: 10.1128/aem.02849-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Broth Microdilution, Etest, and Agar Disk Diffusion Methods for Antimicrobial Susceptibility Testing of Lactobacillus acidophilus Group Members

Abstract: In recent years, the absence of acquired antimicrobial resistance has become an important criterion to evaluate the biosafety of lactobacilli used as industrial starter or probiotic cultures. At present, however, standards for susceptibility testing of Lactobacillus strains or approved guidelines for interpreting the test results are not available. Hence, this study was carried out to contribute to the establishment of a standardized procedure for antimicrobial susceptibility testing of lactobacilli. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 28 publications
(33 reference statements)
1
61
1
3
Order By: Relevance
“…Unlike the participants in the present study, other researchers (3,24) have observed ingrowth of resistant microcolonies in elliptical inhibition zones during Etest analyses of NELAB. Possibly, this may be due to the high rate of spontaneous mutation after prolonged (Ͼ24-to 48-h) incubation with subinhibitory antibiotic concentrations.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Unlike the participants in the present study, other researchers (3,24) have observed ingrowth of resistant microcolonies in elliptical inhibition zones during Etest analyses of NELAB. Possibly, this may be due to the high rate of spontaneous mutation after prolonged (Ͼ24-to 48-h) incubation with subinhibitory antibiotic concentrations.…”
Section: Discussioncontrasting
confidence: 51%
“…In a recent study of Lb. acidophilus group members in which VetMIC was compared to the agar-based disk diffusion and Etest methods, a minor satisfying level of agreement was specifically found for results of susceptibility testing with bacteriostatic agents such as clindamycin (24). In the present study, VetMIC and Etest were compared to broth microdilution as a noncommercial reference method, and MICs of tetracycline, streptomycin, gentamicin, and ampicillin determined by the two assays were in good agreement with those determined by the reference method.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The lack of acquisition of antibiotic resistance has been an important criterion in assessing the safety profile of lactobacilli to be used as probiotics [34], since acquisition of such resistances and their plausible dissemination to the human pathogenic bacteria in the intestine are of great concern [35]. Therefore, it is important to determine the effect on the growth of lactobacilli of antibiotics.…”
Section: Translational Biomedicine Issn 2172-0479mentioning
confidence: 99%
“…Metode disk difusi merupakan salah metode yang direkomendasikan oleh CLSI dalam penentuan nilai konsentrasi minimum. Menurut Mayrhofer et al, (2008) zona hambat yang diperoleh dari metode difusi berkorelasi baik dengan nilai MIC yang diperoleh dari metode dilusi dan E-test. Menurut Singh et al, (2015) metode disk difusi dan makrodilusi juga berkorelasi dengan baik dalam penentuan MIC.…”
Section: Hasil Dan Pembahasan Pengukuran Nilai Micunclassified